INTERVIEW: Knowledge and Terminology Management at Crisplant - Møller, Margrethe H.; Toft, Birthe; Kjeldgaard Almsten, Lisbeth (Communication & Language at Work, 2012)
Margrethe H. Møller interviews Lisbeth Kjeldgaard Almsten (translator/coauthor: Birthe Toft) “If you think that terminology work is simply a matter of buying terminology management software and getting started, you are in for trouble” At Crisplant, we have been doing terminology management for the past 20 years. Today, term bases are used not just for terminology-oriented term management. Recording other types of master data needed by all kinds of professionals in the enterprise is equally important. Within the past year, Crisplant has been acquired by the German BEUMER group, which means that the terminological resources of the two enterprises are in the process of being integrated. The challenges presented by this process demonstrate the importance of adhering to terminological principles when recording terminology resources, while at the same time reminding us what an essential discipline terminology management really is, in enterprise practice as well as in education. Lisbeth Kjeldgaard Almsten Project Manager & Linguistic Coordinator at Crisplant. Lisbeth Kjeldgaard Almsten is dedicated to language technology, and she plays the role of coordinator vis-à-vis her colleagues in the BEUMER Group, who use the same language technology tools as the ones she works with.